Regarding the dead : human remains in the British Museum - Fletcher, Alexandra, (Museum curator); Antoine, Daniel.; Hill, J. D. (British Museum Research Publication ;, 2014)
A key publication on the British Museum's approach to the ethical issues surrounding the inclusion of human remains in museum collections and possible solutions to the dilemmas relating to their curation, storage, access management and display.